TEMPO and RTILs for the sustainable development of TEMPO - mediated alcohol electrooxidation - Delorme, Astrid (2020)
In this thesis, TEMPO-mediated alcohol electrooxidation in room-temperature ionic liquids (RTILs) is described and it is shown that the reactivity and selectivity of the electrocatalytic oxidations can be manipulated by design of the solvent medium. Moreover, higher reaction kinetics and selectivity are obtained in bis(trifluoromethanesulfonyl)imide ([NTf2]–)-based RTILs than in acetonitrile, often the solvent-of-choice in indirect alcohol electrooxidations.